If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(9a + -4b + 6c) = 0 (9a * -7 + -4b * -7 + 6c * -7) = 0 (-63a + 28b + -42c) = 0 Solving -63a + 28b + -42c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-28b' to each side of the equation. -63a + 28b + -28b + -42c = 0 + -28b Combine like terms: 28b + -28b = 0 -63a + 0 + -42c = 0 + -28b -63a + -42c = 0 + -28b Remove the zero: -63a + -42c = -28b Add '42c' to each side of the equation. -63a + -42c + 42c = -28b + 42c Combine like terms: -42c + 42c = 0 -63a + 0 = -28b + 42c -63a = -28b + 42c Divide each side by '-63'. a = 0.4444444444b + -0.6666666667c Simplifying a = 0.4444444444b + -0.6666666667c
| 8/10-7/10 | | 1/7(a-3)(7a+4)=0 | | (4x^2)(3x^5)= | | -3(3y-10)+2(2y+5)= | | 255=x | | 5m+32=5+8(m+6) | | 2+25y-5y^2=x | | -7(n+6)=3(n+6) | | 4(8+r)=4r+32 | | 35=0.5*7 | | 4(7-7x)=28+6x | | 2(4x-.50)=3(x-2) | | 190=60t-5t^2 | | 1/2+5/2 | | -3y=12-2x | | 3(2z-25)-2(z-1)=78 | | 20=4x+3x | | -6(n+1)-2(1-8n)=n-7+8 | | 6+4m=5(m+1) | | 3y+2x=2(y-2x) | | 6(x+9)=8x+8-2x+46 | | 63(5x+4/9)=6(50x-1/3) | | 10+3n=14 | | 6x-9=6(x+9) | | 0.5(x+100)=0.58x-574 | | -16t^2+24t=0 | | 6x-4y=7 | | N/-2=8 | | -4=-10/86+8 | | (7x^3*(2x^2)^2)/(10x^5) | | 3.4x=2.6x+5.6 | | (x/9)=(x/10)-8 |